Acute effect of prolactin on active calcium absorption in rats - N. Krishnamra (2018)
Acute effect of prolactin on active calcium absorption was investigated by using the in vitro everted gut sac technique. An intraperitoneal, administration of a pharmacological dose of 0.02 mg prolactin/100 g body weight 5 or 10 min before the in vitro experiment significantly increased the active calcium transport (represented by the ratio of serosal to mucosal45Ca concentration) only in the duodenum, not in other segments. This prolactin-induced duodenal active transport was seen in 8-week-old sexually mature rats but not in 3-week-old weaned, 5-week-old joung, or > 15-month-old rats. Enhanced apical uptake of45Ca in 2 min by the oil-filled everted duodenal sac from rats that received prolactin 5 and 10 min prior to the experiment further supported the speculation that prolactin could acutely alter the duodenal epithelial handling of calcium.